Liability in BUMDes Bankcruptcy - Kustiono Kastaji (Syntax Corporation Indonesia, 2021)
This research uses judicial normative research methodology since the research is aimed to evaluate the regulations found in the formal rules and regulations related to the BUM Desa or village-owned company and the company bankruptcy, namely Regulations Number 6 year 2014 regarding the Village and Regulations Number 37 year 2004 regarding Bankruptcy and the Deferal of Obligation Payment Code and connect with responsibility of village head. The research conclusions show that: firstly, BUM Desa is initially a business entity without having the status as a legal entity, but during its development, it might have the status of a legal entity. Secondly, Supervisors can be responsible for bankruptcy of BUMDes if it is proven that their fault has caused BUMDes to go Bankruptcy.